1986
DOI: 10.1111/j.1399-6576.1986.tb02480.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic temperature and shivering in epidural anaesthesia

Abstract: The mechanism of shivering during epidural analgesia remains unclear. This study investigates the role of the temperature of the local anaesthetic injected extradurally. Forty patients admitted for elective caesarean section under epidural anaesthesia were studied; 20 were given bupivacaine warmed to 37 degrees C (warm group) and 20 were given bupivacaine stored at 4 degrees C (cold group); the occurrence of shivering in both groups was recorded. The overall incidence of shivering was 27.5%; two patients of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…There is thus the theoretical possibility that injection of relatively cool (i.e., ambient temperature) local anesthetic into the epidural space might provoke shivering by stimulating local temperature sensors. Consistent with this possibility, the incidence of shivering in pregnant women was reported to be greater when they are given refrigerated epidural anesthetic than when the anesthetic is warmed before injection 165. However, epidural administration of large amounts of ice-cold saline does not trigger shivering in non-pregnant volunteers 166.…”
Section: Thermoregulation During Neuraxial Anesthesiamentioning
confidence: 91%
“…There is thus the theoretical possibility that injection of relatively cool (i.e., ambient temperature) local anesthetic into the epidural space might provoke shivering by stimulating local temperature sensors. Consistent with this possibility, the incidence of shivering in pregnant women was reported to be greater when they are given refrigerated epidural anesthetic than when the anesthetic is warmed before injection 165. However, epidural administration of large amounts of ice-cold saline does not trigger shivering in non-pregnant volunteers 166.…”
Section: Thermoregulation During Neuraxial Anesthesiamentioning
confidence: 91%
“…In contrast, other investigators concluded that shivering was primarily caused by a nonthermogenic mechanism. 97,98 A possible detrimental effect of maternal fever on the fetus has been a subject of significant controversy. Macaulay et al 99 monitored intrauterine and fetal scalp temperature in a group of 57 parturients.…”
Section: Fever: Epidural Analgesia and Maternal "Fever"mentioning
confidence: 99%
“…It has been reported that PAS could be prevented by warming skin-surface [6] and warming the administered fluid [7,8], but it is not a perfect way. Many drugs have been shown to be effective on prevention of PAS, such as opioids, α2-agonist, anticholinergic, CNS stimulant, corticosteroid [9], however, few of them were recommended for the prevention of PAS due to various side-effects.…”
Section: Introductionmentioning
confidence: 99%